# NCERT Solution class 7 Mathematics EXERCISE- 1.3

EXERCISE- 1.3

Q1. Find each of the following products:

(a) 3x(-1)

SOLUTION:-

By the rule of Multiplication of integers ,

=3 x (-1)

= -3 ——[(+x-=-)]

(b)  (-1) x 225

SOLUTIONS:-

By the rule of multiplication of integers,

= (-1)x225

= – 225 —-[(-x+=-)]

(c)    (-21)x(-30)

SOLUTION:-

By the rule of multiplication of integers,

= (-21) x (-30)

= 630 —–[(-x-=+)]

(d) (-316) x (-1)

SOLUTION:-

By the rule of multiplication of integers,

= (-316) x(-1)

=316 ——[ (-x-=+)]

(e) (-15) x 0x (-18)

SOLUTION:-

By the rule of multiplication of integer ,

= (-15) x0 x(-18)

= 0

Any integer is multiplied with zero and the answer is zero itself

(f) (-12) x(-11) x(10)

SOLUTION:-

By the rule of multiplication of integer,

= (-12)

x(-11) x(10)

First  multiply the two numbers having the same sign

=132 x 10 —-[(-x-=+)]

= 1320

(g)   9 x (- 3) x(-6)

SOLUTION :-

By the rule of multiplication of integer

= 9x(-3) x(-6)

First multiply the two numbers having same sign

9 x 18 —-[(-x-=+)]

= 162

(h)  (-18) x( -5) x(-4)

SOLUTIONS:-

By the rule of multiplication of integer

= (-18) x (-5) x( – 4 )

First multiply the two numbers having same sign

=  90 x (-4) —-[(-x-=+)]

= -360

(i) (-1) x(-2) x(-3)x 4

SOLUTION:-

By the rule of multiplication of integer

= [ (-1) x (-2) ]x[(-3) x4 ]

= 2x (-12)

= – 24

(j) (-3) x (-6) x(-2) x(-1)

SOLUTIONS:-

By rule of multiplication of integer

= [(-3) x(-6) ]x [(-2) x (- 1)]

First multiply the two numbers having same sign

= 18 x 2    —–[ (-x-=+)

= 36

Q2.  Verify the following :

(a) 18 x [7+(-3)]=[18×7]+[18 x (-3)]

SOLUTION:-

From the given equation

Let us consider the Left Hand Side (LHS) first = 18 x [ 7 +(-3)]

= 18 x [ 7-3]

= 18 x4

= 72

Now consider the Right Hand Side (RHS) = [18 X 7 ] + [ 18 X (-3) ]

= [ 126]+ [-54]

= 126 – 54

=  72

By comparing LHS  and  RHS

72=72

Hence the given equation is verified

(b) (-21)x [(-4)+(-6) ]=[(-21)x(-4)]+[(-21)x(-6)]

SOLUTION:-

From the given equation

Let us consider the Left Hand Side (LHS)first = (-21)x[(-4)+(-6)]

= (-21)x [-4-6]

= (-21)x[-10]

= 210

Now consider the Right Hand Side  (RHS)  = [(-21) x (-4) ]=[(-21) x (-6) ]

=  + 

= 210

By comparing LHS and  RHS

210=210

LHS=RHS

Hence the given equation is verified